Prehospital use of point-of-care tests by community health workers: a scoping review - Ebbs, Daniel; Taricia, Max; Funaro, Melissa C.; O’Daniel, Maggie; Cappello, Michael (Frontiers in Public Health, 2024)
Introduction: Point-of-Care Tests (POCTs) are utilized daily in resource abundant regions, however, are limited in the global south, particularly in the prehospital setting. Few studies exist on the use of non-malarial POCTs by Community Health Workers (CHWs). The purpose of this scoping review is to delineate the current diversity in and breadth of POCTs evaluated in the prehospital setting. Methods: A medical subject heading (MeSH) analysis of known key articles was done by an experienced medical librarian and scoping searches were performed in each database to capture “point of care testing” and “community health workers”. This review was guided by the PRISMA Extension for scoping reviews. Results: 2735 publications were returned, 185 were nominated for full-text review, and 110 studies were confirmed to meet study criteria. Majority focused on malaria (74/110; 67%) or HIV (25/110; 23%); 9/110 (8%) described other tests administered. Results from this review demonstrate a broad geographic range with significant heterogeneity in terminology for local CHWs. Conclusions: The use of new POCTs is on the rise and may improve early risk stratification in limited resource settings. Current evidence from decades of malaria POCTs can guide future implementation strategies.